2014
DOI: 10.1016/j.biortech.2014.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Reductive de-polymerization of kraft lignin for chemicals and fuels using formic acid as an in-situ hydrogen source

Abstract: In this thesis work, formic acid (FA) proved to be an effective in-situ hydrogen donor for the reductive depolymerization of kraft lignin (KL). At the optimum conditions without catalysts, i.e., 300

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 42 publications
(35 reference statements)
2
70
0
Order By: Relevance
“…The use of H-donating reagents/solvents, such as formic acid and other stabilising compounds/alcohols have also been investigated in order to suppress the char formation problem and enhance the operation [20][21][22][23]. Gosselink et al [20] tackled the addition of formic acid as hydrogen donor and experienced an increase in the yield of monomeric aromatics by stabilising the aromatic radicals, up to 12% based on lignin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of H-donating reagents/solvents, such as formic acid and other stabilising compounds/alcohols have also been investigated in order to suppress the char formation problem and enhance the operation [20][21][22][23]. Gosselink et al [20] tackled the addition of formic acid as hydrogen donor and experienced an increase in the yield of monomeric aromatics by stabilising the aromatic radicals, up to 12% based on lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Gosselink et al [20] tackled the addition of formic acid as hydrogen donor and experienced an increase in the yield of monomeric aromatics by stabilising the aromatic radicals, up to 12% based on lignin. Huang et al [22] adopted the formic acid as well as an in situ hydrogen source during the depolymerisation of kraft lignin. It was demonstrated in this study that the formic acid is a more reactive hydrogen source than external hydrogen towards the reductive depolymerisation of technical lignin streams.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen donor solvents could result in the use of relatively lower working temperatures (220–300°C) than those needed for hydrotreating with gaseous hydrogen (up to 500°C) . Furthermore, hydrogen donor solvents can increase the degraded lignin yield and prevent char formation by avoiding repolymerization of reaction intermediates …”
Section: Methodsmentioning
confidence: 99%
“…In the studies using gaseous hydrogen, the use of high temperatures (>420°C) has been found to promote depolymerization into monomeric compounds like phenols or hydrocarbons . In the case of hydrogen donor solvents, low reaction temperatures (<300°C) cause only negligible effects in the lignin degradation yield . At higher temperatures, charring and repolymerization takes place, reducing the product yield from around 90% to 34%, even though the average molecular weight continues to decrease with increasing temperatures even above 300°C …”
Section: Methodsmentioning
confidence: 99%
“…[24] Notably,ethanol also acts as an effective hydrogen donor through hydride transfer of its a-hydrogen. [24] Notably,ethanol also acts as an effective hydrogen donor through hydride transfer of its a-hydrogen.…”
Section: Catalytic Deconstruction Of Ligninmentioning
confidence: 99%